Preoperative Management of Chronic Rhinosinusitis Prior to Office Balloon Sinus Dilation: A 2011–2014 MarketScan® Analysis. Issue 4 (July 2019) - Jang, David W.; Abraham, Cecily; Cyr, Derek D.; Schulz, Kristine; Abi Hachem, Ralph; Witsell, David L.
Background: In-office balloon sinus dilation (BSD) has recently gained popularity as a surgical treatment option for chronic rhinosinusitis (CRS). However, utilization, indications, and practice patterns surrounding in-office BSD remain unclear. Objective: The purpose of this study was to use a large national administrative database to assess preoperative management of CRS prior to in-office BSD. Methods: Patients undergoing standalone in-office BSD from 2011 to 2014 were identified on MarketScan and compared to a control group undergoing functional endoscopic sinus surgery (FESS). Visits to the otolaryngologist, number of computed tomography (CT) scans, number of antibiotic and steroid prescriptions, and duration of time from first visit to procedure were compared. Results: When compared to the FESS group, the in-office BSD group overall had fewer office visits (2.0 vs 2.2), CT scans (1.0 vs 1.1), prescriptions for antibiotics (2.0 vs 2.2), prescriptions for systemic steroids (1.5 vs 1.8), and topical steroids (1.4 vs 1.5) in the preoperative period. They also had a shorter mean duration of time between first visit and CT scan (17.5 vs 21.4 days) as well as between first visit and procedure (55.0 vs 67.8 days). All of these findings were statistically significant. Conclusion: In-office BSD for CRS was overall associated with less intense management in the preoperative period when compared to FESS. Such differences may reflect ongoing shifts in practice patterns and need to be further investigated.